COVID-19 vaccine misinformation in English-language news media: retrospective cohort study. Issue 6 (1st June 2022) - Lurie, Peter; Adams, Jordan; Lynas, Mark; Stockert, Karen; Carlyle, Robyn Correll; Pisani, Amy; Evanega, Sarah Davidson
Abstract : Objectives: To describe COVID-19 vaccine misinformation and track trends over time in traditional news media. Design: Retrospective cohort study of a large database of online articles, July 2020–June 2021. Setting: English-language articles from 100 news outlets with the greatest reach. Main outcome measures: Numbers and percentages of articles containing COVID-19 vaccine misinformation over the study period. Further analysis by misinformation themes and whether articles included primary misinformation, fact-checking or simply referred to misinformation. Results: 41 718 (3.2% of all COVID-19 vaccine articles) contained at least one of the vaccine misinformation themes based on the Boolean string developed for this study. The volume of such articles increased beginning in November 2020, but their percentage of all articles remained essentially stable after October 2020. 56.2% contained at least one mention of a safety theme, followed by development, production, and distribution (26.6%), and conspiracies (15.1%). Of 500 articles through January 2021 randomly selected from those identified by the Boolean string, 223 were not relevant, and 277 included either fact-checking (175 articles), refers to misinformation (87 articles) or primary misinformation (15 articles). In eight study weeks, the reach of these 277 articles (defined as visitors to the sites containing the articles) exceeded 250 million people. Fact-checking accounted for 69.6% of all reach for these articles and the number of such articles increased after November 2020. Overall, approximately 0.1% (95% CI 0.05% to 0.16%) of all articles on COVID-19 vaccines in our sample contained primary misinformation. Conclusions: COVID-19 vaccine misinformation in traditional news media is uncommon but has the capacity to reach large numbers of readers and affect the vaccine conversation. Recent increases in fact-checking may counteract some of the misinformation currently circulating.